Cover Image. (May 2016) - Pandruvada, Subramanya N.; Gonzalez, Octavio A.; Kirakodu, Sreenatha; Gudhimella, Sudha; Stromberg, Arnold J.; Ebersole, Jeffrey L.; Orraca, Luis; Gonzalez‐Martinez, Janis; Novak, Michael J.; Huja, Sarandeep S.
Abstract : The cover image, by Sarandeep Huja et al., is based on the Animal Experiment Bone biology‐related gingival transcriptome in ageing and periodontitis in non-human primates, DOI:10.1111/jcpe.12528 .